EFEKTIVITAS PEMBERIAN JUS BUAH BIT TERHADAP KADAR HEMOGLOBIN IBU HAMIL DENGAN ANEMIA - Wenda Stephana; Sri Utami; Veny Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The aim of this research is to analize the effectiveness of beetroot juice of hemoglobin levels for pregnant women withanemia. The research used quasy experiment design with non-equivalent control group which is divided intoexperimental group and control group. The research was conducted on pregnant women in the “Puskesmas PekanbaruKota”. The sample of this research is taken by using purposive techniques sampling which is selected based oninclusion criteria. The instrument of this research digital levels of hemoglobin gauges. Data then analyzed intounivariate and bivariate with independent and dependent sample t test. The result showed that of juice beet ofhemoglobin levels for pregnant women with anemia with p value (0,000) < α (0,05). The result of this researchrecommend health care to give promotion about complementary for pregnant women consume of beet juice.Keywords : anemia, beetroot juice, hemoglobin, pregnant women